2019
DOI: 10.31557/apjcp.2019.20.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate of Colorectal Cancer in Iran: A Systematic Review and Meta-Analysis

Abstract: 2015). CRC is one of the most common cancers in Iran, which has increased in recent years. The incidence of this cancer in Iran is lower than other developed countries; however, in-recent decades, this rate has increased significantly. According to national reports of Iran cancer registration in 2009, colorectal cancer is the third most common cancer in women and the fourth most common cancer in men

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
1
30
1
Order By: Relevance
“…In a meta-analysis study, which was recently done by Maajani et al in Iran, it was suggested that the paramount 1-year survival rate in Iran was colon cancer which was estimated to be near 90%. 77 In meta-regression analysis, which was conducted in this study, there was no significant correlation between the survival rate of CRC with sample size, the year which the studies were conducted in and the Human Development Index of the countries. Several factors can affect the survival rate of colorectal cancer in these measures.…”
Section: Discussionmentioning
confidence: 58%
“…In a meta-analysis study, which was recently done by Maajani et al in Iran, it was suggested that the paramount 1-year survival rate in Iran was colon cancer which was estimated to be near 90%. 77 In meta-regression analysis, which was conducted in this study, there was no significant correlation between the survival rate of CRC with sample size, the year which the studies were conducted in and the Human Development Index of the countries. Several factors can affect the survival rate of colorectal cancer in these measures.…”
Section: Discussionmentioning
confidence: 58%
“…According to the study (32)(33)(34), which showed diabetes mellitus increases the chances of developing colorectal cancer, colorectal cancer is a common and fatal illness with a high incidence of occurrence in different parts of the world and is the third leading cause of cancer deaths in the world (45). Cancer occurs when parts of the body begin to grow uncontrollably.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of gastric cancer is closely related to the timing of diagnosis and treatment. The 5-year survival rate of patients with advanced gastric cancer is still less than 30% even if they receive comprehensive treatment mainly by surgery (2)(3)(4)(5). Early diagnosis of gastric cancer can make the clinical stage of the tumor move forward, reduce the transformation to advanced cancer, improve the early treatment rate and the overall cure rate of gastric cancer, which can not only save but also improve the consumption quality of medical resources (6).…”
Section: Introductionmentioning
confidence: 99%